Use of Son-Rise Program and Applide Behavior Analysis (ABA) Method on Language Development of Children with Autism - Siti Annoora Niroha Pulungan; Imas Diana Aprilia; Oom Sitti Homdidjah (Jurnal Indonesia Sosial Teknologi, 2024)
There are various approaches that can be used in language development in children with autism. Son-Rise programs and Applide Behavior Analysis (ABA) methods are approaches that can be used in the language development of children with autism. The author discusses matters related to the Use of Son-Rise programs and Applide Behavior Analysis (ABA) Methods for Language Development of Children with Autism. Aims to describe son-rise programs and Applide Behavior Analysis (ABA) Methods for object language development. The results of the discussion were how to use the Son-Rise program and the Applide Behavior Analysis (ABA) Method for Language Development of Children with Autism.